Production, Characterization, and Function of Pseudoislets from Perinatal Canine Pancreas. Issue 12 (December 2019) - Czernichow, P.; Reynaud, K.; Kerr-Conte, J.; Furthner, E.; Ravassard, P.
We evaluated the cell composition and function of canine pancreatic pseudoislets (PIs) produced from 42- to 55-day-old fetuses, 1- to 21-day-old pups, and an adult dog pancreas. After mild collagenase treatment, partially digested tissues were cultured for 2–3 weeks. PI production started on culture day 3, was marked for 6 to 9 days, and then stopped. PI production was greatest with the neonatal specimens, reaching about 12 million aggregates per litter (55-day-old fetus) or per pancreas (1-day-old pup). Cell composition at all stages was similar to that in adult pancreatic islets, with predominant β cells, scant α cells and, most importantly, presence of δ cells. Among pancreatic markers assessed by quantitative real-time PCR (qRT-PCR) mRNA assay, insulin showed the highest expression levels in PIs from newborn and adult pancreas, although these were more than 1000 times lower than in adult islets. Pdx1 mRNA expression was high in PIs from 55-day-old pancreases and was lower at later stages. Consistent with the qRT-PCR results, the insulin content was far lower than reported in adult dog pancreatic islets. However, insulin release by PIs from 1-day-old pups was demonstrated and was stimulated by a high-glucose medium. PIs were transplanted into euglycemic and diabetic SCID mice. In euglycemic animals, the transplant cell composition underwent maturation and transplants were still viable after 6 months. In diabetic mice, the PI transplants produced insulin and partially controlled the hyperglycemia. These data indicate that PIs can be produced ex vivo from canine fetal or postnatal pancreases. Although functional PIs can be obtained, the production yield is most likely insufficient to meet the requirements for diabetic dog transplantation without further innovation in cell culture amplification.